A high-entropy alloy and a high-entropy alloy article and a method of making the same

CN122959596APending Publication Date: 2026-10-23CITY UNIVERSITY OF HONG KONG SHENZHEN FUTIAN RESEARCH INSTITUTE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510503440.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-21
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0006]为解决上述技术问题,本发明的目的在于提供一种高熵合金与高熵合金制品及其制备方法,在得到组织均匀、致密度高的材料的同时,有效解决难熔高熵合金成型性差和易开裂的问题

Benefits of technology

[0045]本发明通过调控高熵合金中轻质元素与难熔元素的比例,并创造性地添加少量稀土元素,能够得到一种成分均匀且晶粒细化效果较好的高熵合金,并且,通过进一步结合对激光功率、扫描速度、扫描间距、层厚等选区激光熔化的参数的调控,直接获得组织均匀、致密度高的新型轻质高强高熵合金制品,在实现高熵合金制品轻质与高温高强相结合的同时,解决了高熵合金成型性差、易开裂的问题,且经过验证也未出现成分偏析,晶粒细化效果较好。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122959596A_ABST
    Figure CN122959596A_ABST
Patent Text Reader

Abstract

The application provides a high-entropy alloy, a high-entropy alloy product and a preparation method thereof. The high-entropy alloy is composed of Zr, V, Nb, Ti, Al and Sc elements, and the molar composition is: Zr (1.0‑1.5) V (0.6‑1.0) Nb (0.8‑1.2) Ti (3.4‑3.8) Al (0.4‑0.8) Sc (0.05‑0.3) The application directly obtains a new light high-strength high-entropy alloy product with uniform structure and high density by regulating the ratio of light elements and refractory elements in the high-entropy alloy, creatively adding a small amount of rare earth elements, and further regulating the parameters of selective laser melting such as laser power, scanning speed, scanning interval and layer thickness. The high-entropy alloy product has higher size precision and more flexible structure design, and can realize direct forming of aerospace parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a high-entropy alloy, high-entropy alloy products, and their preparation methods, belonging to the field of metallurgical technology. Background Technology

[0002] Refractory high-entropy alloys, due to their high melting point, high strength, and excellent thermal stability, can be used at temperatures of 800℃ or even higher. Especially for high-entropy alloys containing a certain proportion of Ti and Al, they hold promise as a replacement for traditional titanium-aluminum alloys, becoming a new generation of materials for the aerospace field. However, when manufacturing refractory high-entropy alloys using traditional arc melting methods, problems such as coarse alloy grains, severe compositional segregation, and difficulties in subsequent casting are unavoidable.

[0003] Laser additive manufacturing (LAM) involves melting alloy powder with a high-energy laser and depositing it layer by layer, enabling direct material shaping and allowing for the manufacture of difficult-to-machine metals with greater structural flexibility. Furthermore, this technology boasts high energy density and rapid heating / cooling rates, which help suppress compositional segregation and refine grains, making it a relatively ideal method for preparing refractory high-entropy alloys. However, LAM still faces challenges in preparing refractory high-entropy alloys, including limited formability and susceptibility to cracking due to significant room-temperature brittleness. Therefore, addressing the issues of poor formability and cracking in LAM during laser additive manufacturing is crucial for obtaining high-performance alloy materials and realizing their applications. Most methods for improving the mechanical properties of high-entropy alloys typically involve solution heat treatment followed by aging heat treatment; however, this not only increases production complexity and prolongs the production cycle but also hinders practical mass production.

[0004] CN117259783A discloses a method for laser additive manufacturing of high-strength, high-toughness, refractory, high-entropy alloys and the resulting products. The method develops Nb alloys... 40 Ta 25 Ti 15 Hf 15 Zr5 possesses high hardness, strength, and good ductility. By directly employing large-size mixed-element powders and laser remelting using laser deposition technology, a good metallurgical bond between high-melting-point refractory elements can be achieved. However, this preparation method is cumbersome and energy-intensive, resulting in an alloy density exceeding 11 g / cm³. 3 This makes it difficult to meet the application requirements of aerospace materials.

[0005] Therefore, it is of great significance to achieve a combination of lightweight and high strength in high-entropy alloy materials while solving the problems of poor formability and easy cracking in laser additive manufacturing of refractory high-entropy alloys. Summary of the Invention

[0006] To address the aforementioned technical problems, the present invention aims to provide a high-entropy alloy, high-entropy alloy products, and a method for preparing the same, which effectively solves the problems of poor formability and easy cracking of refractory high-entropy alloys while obtaining materials with uniform structure and high density.

[0007] To achieve the above objectives, the present invention provides a high-entropy alloy, wherein the high-entropy alloy is composed of Zr, V, Nb, Ti, Al and Sc elements, and its molar composition is Zr (1.0-1.5) V (0.6-1.0) Nb (0.8-1.2) Ti (3.4-3.8) Al (0.4-0.8) Sc (0.05-0.3 ).

[0008] For high-entropy alloys, altering their alloying element composition, proportions, or adding microalloying elements can significantly affect their microstructure or properties. This invention, based on the practical application requirements of aerospace materials, rationally incorporates Zr, V, Nb, Ti, Al, and Sc, which can pin grain boundaries. It also features lightweight, high-temperature, and high-strength alloy design, making it more suitable for various applications. Furthermore, the high-entropy alloy of this invention is relatively uniform, and verification has shown no compositional segregation, indicating good grain refinement.

[0009] According to a specific embodiment of the present invention, preferably, the high-entropy alloy has an alloy composition of Zr. 1.2 V 0.8 NbTi 3.6 Al 0.6 Sc 0.1 .

[0010] According to a specific embodiment of the present invention, preferably, the density of the high-entropy alloy is less than 6 g / cm³. 3 More preferably, it is below 5.442 g / cm³. 3 This density refers to the theoretical density of high-entropy alloys, which is determined by the alloy composition.

[0011] According to a specific embodiment of the present invention, preferably, the density of the high-entropy alloy is ≥99%.

[0012] Secondly, the present invention also provides a method for preparing a high-entropy alloy product, wherein the above-mentioned high-entropy alloy is used as raw material.

[0013] According to a specific embodiment of the present invention, preferably, the preparation method includes the following steps:

[0014] High-entropy alloy ingots are powdered and selectively laser-melted to obtain high-entropy alloy products.

[0015] The laser power of the selected area laser melting is 190-280W, the scanning speed is 1200-1500mm / s, the selected layer thickness is 0.02-0.04mm, the scanning interval is 0.06-0.10mm, and the scanning angle is 65°-70°.

[0016] The high-entropy alloy powder selected after powdering in the preparation method has a particle size distribution of 53-100 μm.

[0017] In the above-mentioned method for preparing high-entropy alloy products, preferably, the laser power of the selective laser melting is 190-280W, the scanning speed is 1400mm / s, the selected layer thickness is 0.03mm, the scanning interval is 0.08mm, and the scanning angle is 67°.

[0018] This invention utilizes selective laser melting (SLM) with a laser as the heat source, enabling rapid melting and solidification of metal powder to obtain high-entropy alloy products with extremely high density. Furthermore, by adjusting parameters such as laser power and scanning speed, the microstructure and properties can be controlled, simplifying subsequent processing and significantly reducing complex procedures. This results in high-entropy alloy products with higher dimensional accuracy and more flexible structural design, enabling direct molding of aerospace components. The alloy composition and corresponding molar ratio in this invention, combined with appropriate SLM process parameters, can achieve a high density of over 99%.

[0019] In the above-mentioned method for preparing high-entropy alloy products, preferably, the energy density of the laser is 48-168 J / mm². 3 When using a laser with an energy density within the above-mentioned range for fabrication, good forming results can be achieved.

[0020] In the above-mentioned method for preparing high-entropy alloy products, preferably, the scanning method is strip-shaped, specifically a strip type.

[0021] In the above-mentioned method for preparing high-entropy alloy products, preferably, the high-entropy alloy ingot is prepared by the following steps:

[0022] Zr, V, Nb, Ti, Al and Sc are placed in the induction melt in order of increasing melting point;

[0023] The high-entropy alloy ingot is obtained by melting at 1600-1800℃ for 18-20 minutes under a protective atmosphere.

[0024] In the above-mentioned method for preparing high-entropy alloy products, preferably, the high-entropy alloy ingot is prepared by the following steps:

[0025] First, Zr, V, Nb, Ti, Al and Sc with a purity of not less than 99.9 wt.% are polished to remove oxide scale, ultrasonically cleaned and dried. They are then weighed according to the molar ratio. Then, the proportioned metal raw materials are placed in the induction melt in order of melting point from low to high.

[0026] Under a protective atmosphere, at 1600-1800℃, the alloy is first roughly melted for 14-16 minutes, then refined for 4-6 minutes, and repeated several times (e.g., 4 times). After that, it is cast and cooled in the furnace to obtain the ingot of the high-entropy alloy.

[0027] The protective atmosphere is generally argon, and the induction furnace is a magnetic levitation vacuum induction melting furnace.

[0028] In the above-mentioned method for preparing high-entropy alloy products, preferably, the method further includes the following steps: cutting the high-entropy alloy ingot, grinding it, and then performing gas atomization powdering to screen powder with a particle size of 53-100μm; the specific steps may include: cutting the high-entropy alloy ingot into strips, grinding it to remove oxide scale, and then performing gas atomization powdering to screen powder with a particle size of 53-100μm.

[0029] In the above-mentioned method for preparing high-entropy alloy products, preferably, the selected area laser melting specifically includes:

[0030] Preparations before printing;

[0031] The quantity, size, and placement of the printed parts on the substrate are determined based on the powder characteristics and the actual equipment model.

[0032] The laser power for selective laser melting is set to 190-280W, the scanning speed to 1200-1500mm / s, the selected layer thickness to 0.02-0.04mm, the scanning interval to 0.06-0.10mm, the scanning angle to 65°-70°, and the scanning method to be strip-shaped; more preferably, the scanning speed is 1400mm / s, the selected layer thickness is 0.03mm, the scanning interval is 0.08mm, the scanning angle is 67°, and the scanning method to be strip-shaped.

[0033] Turn on the laser and start printing once the laser has stabilized.

[0034] In the above-mentioned method for preparing high-entropy alloy products, preferably, the pre-printing preparation work includes: selecting titanium alloy as the printing substrate according to the properties of the printing material, cleaning it and placing it into the forming rod; putting an appropriate amount of high-entropy alloy powder into the powder cylinder; adjusting the position of the scraper; pre-spreading powder until the alloy powder covers the substrate; closing the door and introducing argon gas to remove oxygen.

[0035] As a preferred embodiment, the method for preparing high-entropy alloy products provided by the present invention includes the following specific steps:

[0036] Zr, V, Nb, Ti, Al and Sc are placed in the induction melt in order of increasing melting point;

[0037] The high-entropy alloy ingot is obtained by melting at 1600-1800℃ for 18-20 minutes under a protective atmosphere.

[0038] The high-entropy alloy ingots are powdered for use in selective laser melting.

[0039] Preparations before printing;

[0040] The quantity, size, and placement of the printed parts on the substrate are determined based on the powder characteristics and the actual equipment model.

[0041] The laser power for selective laser melting is set to 190-280W, the scanning speed to 1200-1500mm / s, the selected layer thickness to 0.02-0.04mm, the scanning interval to 0.06-0.10mm, and the scanning angle to 65°-70°; more preferably, the scanning speed is 1400mm / s, the selected layer thickness is 0.03mm, the scanning interval is 0.08mm, the scanning angle is 67°, and the scanning method is strip-shaped.

[0042] Turn on the laser and start printing after the laser stabilizes. The entire printing process is carried out under argon protection, with the oxygen content (volume fraction) controlled at 10%. -3 the following.

[0043] Thirdly, the present invention also provides a high-entropy alloy product prepared by the above-described preparation method.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] This invention, by controlling the ratio of lightweight elements to refractory elements in a high-entropy alloy and creatively adding a small amount of rare earth elements, can obtain a high-entropy alloy with uniform composition and good grain refinement. Furthermore, by further combining the control of selected area laser melting parameters such as laser power, scanning speed, scanning spacing, and layer thickness, a novel lightweight high-strength high-entropy alloy product with uniform structure and high density can be directly obtained. While achieving the combination of lightweight and high-temperature and high-strength high-entropy alloy products, it solves the problems of poor formability and easy cracking of high-entropy alloys. Moreover, it has been verified that no compositional segregation has been observed, and the grain refinement effect is good.

[0046] The high-entropy alloy products of this invention have higher dimensional accuracy and more flexible structural design, enabling direct molding of aerospace parts. Attached Figure Description

[0047] Figure 1The images shown are optical microscopy images, electron backscatter diffraction images, and energy dispersive spectroscopy analysis results of the high-entropy alloy product of Example 1.

[0048] Figure 2 The images shown are optical microscopy images, electron backscatter diffraction images, and energy dispersive spectroscopy analysis results of the high-entropy alloy product in Example 2.

[0049] Figure 3 The images shown are optical microscope images and electron backscatter diffraction images of the high-entropy alloy product in Comparative Example 1. Detailed Implementation

[0050] In order to provide a clearer understanding of the technical features, objectives and beneficial effects of the present invention, the technical solution of the present invention will now be described in detail below, but it should not be construed as limiting the scope of implementation of the present invention.

[0051] Example 1

[0052] This embodiment provides a high-entropy alloy Zr 1.2 V 0.8 NbTi 3.6 Al 0.6 Sc 0.1 The high-entropy alloy products are prepared through the following steps:

[0053] Ingredients: Zr, V, Nb, Ti, Al, and Sc with a purity of not less than 99.9 wt.% are ground to remove oxide scale, ultrasonically cleaned, and dried. According to Zr... 1.2 V 0.8 NbTi 3.6 Al 0.6 Sc 0.1 Weigh various metal raw materials according to the molar ratio;

[0054] Smelting: The proportioned metal raw materials are placed into the magnetic levitation vacuum induction melting furnace in order of increasing melting point; the oxygen content (volume fraction) is evacuated to 5×10⁻⁶. -3 The following steps involve heating the furnace to 1800℃ to fully melt the alloy, performing rough melting for 15 minutes, followed by refining for 5 minutes. This process of "rough melting + refining" is repeated four times before the alloy is cast and cooled in the furnace. The entire melting process is carried out under the protection of high-purity argon gas, resulting in a uniform large-size high-entropy alloy ingot with a diameter of approximately 163 mm and a thickness of approximately 86 mm.

[0055] Powder preparation: The above-mentioned ingot is cut into strips with dimensions of 10×10×80mm, and after further grinding to remove oxide scale, it is subjected to gas atomization powder preparation to obtain powder with a particle size of 53-100μm, which is ready for selective laser melting.

[0056] Selective laser melting specifically includes:

[0057] (1) Pre-printing preparation: Select titanium alloy as the printing substrate according to the properties of the printing material, clean it and put it into the forming bar; put an appropriate amount of high-entropy alloy powder into the powder cylinder; adjust the position of the scraper; pre-spread the powder until the alloy powder covers the substrate; close the door and introduce argon gas to remove oxygen;

[0058] (2) Set the quantity, size and placement of the printed parts on the substrate according to the powder characteristics and the actual equipment model;

[0059] (3) Set the laser power for selective laser melting to 190W, the scanning speed to 1400mm / s, the selected layer thickness to 0.03mm, the scanning interval to 0.08mm, the scanning angle to 67°, the scanning path to a strip shape, and the energy density to approximately 56.5J / mm². 3 ;

[0060] (4) Turn on the laser and start printing after the laser stabilizes. The entire printing process is carried out under argon protection, and the oxygen content (volume fraction) is controlled at 10%. -3 The following steps lead to the final high-entropy alloy product.

[0061] The high-temperature, high-entropy alloy Zr in this embodiment 1.2 V 0.8 NbTi 3.6 Al 0.6 Sc 0.1 Lightweight and high-strength, with good formability, and a theoretical density of 5.442 g / cm³. 3 The density exceeds 99%; its optical microscopy images, electron backscatter diffraction, and energy dispersive spectroscopy analysis results are as follows: Figure 1 As shown, by Figure 1 It can be seen that the obtained high-entropy alloy products do not have obvious defects such as microcracks, keyholes, inclusions or unmelted particles. The microstructure is fine, the grains are evenly distributed and there is no obvious compositional segregation.

[0062] Example 2

[0063] This embodiment provides a high-entropy alloy Zr 1.2 V 0.8 NbTi 3.6 Al 0.6 Sc 0.1 The high-entropy alloy products are prepared through the following steps:

[0064] Ingredients: Zr, V, Nb, Ti, Al, and Sc with a purity of not less than 99.9 wt.% are ground to remove oxide scale, ultrasonically cleaned, and dried. According to Zr... 1.2 V 0.8 NbTi 3.6 Al 0.6 Sc 0.1 Weigh various metal raw materials according to the molar ratio;

[0065] Smelting: The proportioned metal raw materials are placed into the magnetic levitation vacuum induction melting furnace in order of increasing melting point; the oxygen content (volume fraction) is evacuated to 5×10⁻⁶. -3 The following steps involve heating the furnace to 1800℃ to fully melt the alloy, performing rough melting for 15 minutes, followed by refining for 5 minutes. This process of "rough melting + refining" is repeated four times before the alloy is cast and cooled in the furnace. The entire melting process is carried out under the protection of high-purity argon gas, resulting in a uniform large-size high-entropy alloy ingot with a diameter of approximately 163 mm and a thickness of approximately 86 mm.

[0066] Powder preparation: The above-mentioned ingot is cut into strips with dimensions of 10×10×80mm, and after further grinding to remove oxide scale, it is subjected to gas atomization powder preparation to obtain powder with a particle size of 53-100μm, which is ready for selective laser melting.

[0067] Selective laser melting specifically includes:

[0068] (1) Pre-printing preparation: Select titanium alloy as the printing substrate according to the properties of the printing material, clean it and put it into the forming bar; put an appropriate amount of high-entropy alloy powder into the powder cylinder; adjust the position of the scraper; pre-spread the powder until the alloy powder covers the substrate; close the door and introduce argon gas to remove oxygen;

[0069] (2) Set the quantity, size and placement of the printed parts on the substrate according to the powder characteristics and the actual equipment model;

[0070] (3) Set the laser power for selective laser melting to 280W, the scanning speed to 1400mm / s, the selected layer thickness to 0.03mm, the scanning interval to 0.08mm, the scanning angle to 67°, the scanning path to a strip shape, and the energy density to approximately 83.3J / mm². 3 ;

[0071] (4) Turn on the laser and start printing after the laser stabilizes. The entire printing process is carried out under argon protection, and the oxygen content (volume fraction) is controlled at 10%. -3 The following steps lead to the final high-entropy alloy product.

[0072] The high-temperature, high-entropy alloy Zr in this embodiment 1.2 V 0.8 NbTi 3.6 Al 0.6 Sc 0.1 Lightweight and high-strength, with good formability, and a theoretical density of 5.442 g / cm³. 3 The density exceeds 99%; its optical microscopy images, electron backscatter diffraction, and energy dispersive spectroscopy analysis results are as follows: Figure 2 As shown, by Figure 2It can be seen that the obtained high-entropy alloy products do not have obvious defects such as microcracks, keyholes, inclusions or unmelted particles; the microstructure is fine, the grains are evenly distributed and there is no obvious compositional segregation.

[0073] Comparative Example

[0074] This comparative example provides a high-entropy alloy Zr 1.2 V 0.8 NbTi 3.6 Al 0.6 Sc 0.1 The high-entropy alloy products are prepared through the following steps:

[0075] Ingredients: Zr, V, Nb, Ti, Al, and Sc with a purity of not less than 99.9 wt.% are ground to remove oxide scale, ultrasonically cleaned, and dried. According to Zr... 1.2 V 0.8 NbTi 3.6 Al 0.6 Sc 0.1 Weigh various metal raw materials according to the molar ratio;

[0076] Smelting: The proportioned metal raw materials are placed into the magnetic levitation vacuum induction melting furnace in order of increasing melting point; the oxygen content (volume fraction) is evacuated to 5×10⁻⁶. -3 The following steps involve heating the furnace to 1800℃ to fully melt the alloy, performing rough melting for 15 minutes, followed by refining for 5 minutes. This process of "rough melting + refining" is repeated four times before the alloy is cast and cooled in the furnace. The entire melting process is carried out under the protection of high-purity argon gas, resulting in a uniform large-size high-entropy alloy ingot with a diameter of approximately 163 mm and a thickness of approximately 86 mm.

[0077] Powder preparation: The above-mentioned ingot is cut into strips with dimensions of 10×10×80mm, and after further grinding to remove oxide scale, it is subjected to gas atomization powder preparation to obtain powder with a particle size of 53-100μm, which is ready for selective laser melting.

[0078] Selective laser melting specifically includes:

[0079] (1) Pre-printing preparation: Select titanium alloy as the printing substrate according to the properties of the printing material, clean it and put it into the forming bar; put an appropriate amount of high-entropy alloy powder into the powder cylinder; adjust the position of the scraper; pre-spread the powder until the alloy powder covers the substrate; close the door and introduce argon gas to remove oxygen;

[0080] (2) Set the quantity, size and placement of the printed parts on the substrate according to the powder characteristics and the actual equipment model;

[0081] (3) Set the laser power for selective laser melting to 280W, the scanning speed to 1000mm / s, the selected layer thickness to 0.03mm, the scanning interval to 0.08mm, the scanning angle to 67°, the scanning path to a strip shape, and the energy density to approximately 83.3J / mm². 3 ;

[0082] (4) Turn on the laser and start printing after the laser stabilizes. The entire printing process is carried out under argon protection, and the oxygen content (volume fraction) is controlled at 10%. -3 The following steps lead to the final high-entropy alloy product.

[0083] This comparative example features a high-entropy alloy Zr. 1.2 V 0.8 NbTi 3.6 Al 0.6 Sc 0.1 Its formability is poor; its optical microscopy images and electron backscattering diffraction results are as follows: Figure 3 As shown, by Figure 3 It can be seen that the obtained high-entropy alloy products have low density, are covered with large-sized pores, and even have serious defects such as keyholes and microcracks; the grain size and grain morphology vary greatly in different locations, and the microstructure is extremely uneven.

[0084] The high-entropy alloy products of this invention have uniform structure and high density. While achieving a combination of lightweight and high strength at high temperature, they solve the problems of poor formability and easy cracking of high-entropy alloys. Furthermore, it has been verified that no component segregation has occurred and the grain refinement effect is also good.

Claims

1. A high-entropy alloy, wherein, The high-entropy alloy is composed of Zr, V, Nb, Ti, Al, and Sc elements, with a molar composition of Zr. (1.0-1.5) V (0.6-1.0) Nb (0.8-1.2) Ti (3.4-3.8) Al (0.4-0.8) Sc (0.05-0.3) .

2. The high-entropy alloy according to claim 1, wherein, The high-entropy alloy has the following alloy composition: Zr 1.2 V 0.8 NbTi 3.6 Al 0.6 Sc 0.1 .

3. The high-entropy alloy according to claim 1, wherein, The density of the high-entropy alloy is less than 6 g / cm³. 3 .

4. The high-entropy alloy according to claim 1, wherein, The high-entropy alloy has a density of ≥99%.

5. A method for preparing a high-entropy alloy product, wherein the method uses the high-entropy alloy as described in any one of claims 1-4 as raw material.

6. The method for preparing high-entropy alloy products according to claim 5, wherein, The preparation method includes the following steps: High-entropy alloy ingots are powdered and selectively laser-melted to obtain high-entropy alloy products. The laser power of the selected area laser melting is 190-280W, the scanning speed is 1200-1500mm / s, the selected layer thickness is 0.02-0.04mm, the scanning interval is 0.06-0.10mm, and the scanning angle is 65°-70°. The high-entropy alloy powder selected after powdering in the preparation method has a particle size distribution of 53-100 μm.

7. The method for preparing high-entropy alloy products according to claim 6, wherein, The energy density of the laser is 48-168 J / mm². 3 ; And / or, the scanning method is bar scanning.

8. The method for preparing high-entropy alloy products according to claim 6, wherein, The high-entropy alloy ingot is prepared using the following steps: Zr, V, Nb, Ti, Al and Sc are placed in the induction melt in order of increasing melting point; The high-entropy alloy ingot is obtained by melting at 1600-1800℃ for 18-20 minutes under a protective atmosphere.

9. The method for preparing high-entropy alloy products according to claim 6, wherein, The preparation method further includes the following steps: cutting the high-entropy alloy ingot, grinding it, and then performing gas atomization powdering to screen powder with a particle size of 53-100μm.

10. A high-entropy alloy article prepared by the preparation method according to any one of claims 5-9.

Citation Information

Patent Citations

  • Method for manufacturing high-toughness refractory high-entropy alloy through laser additive and product of high-toughness refractory high-entropy alloy

    CN117259783A